Republic of Uzbekistan : Technical Assistance Report-External Sector Statistics Mission (September 30-October 11, 2010). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
At the request of the Republic of Uzbekistan authorities for technical assistance (TA) on external sector statistics (ESS), and with the support of the Middle East and Central Asia Department (MCD) of the International Monetary Fund (IMF), a mission from the IMF Statistics Department (STA) visited Tashkent from September 30 through October 11, 2019. This was the second TA mission under the auspices of the Data for Decisions Fund and the third since the Presidential Order of September 12, 2017, on Measures to Ensure the Accessibility and Openness of Economic and Financial Data for the Republic of Uzbekistan was issued.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet